2015
DOI: 10.1242/jeb.132191
|View full text |Cite
|
Sign up to set email alerts
|

Life history trade-offs imposed by dragline use in two money spiders

Abstract: Trade-offs among life history traits are central to understanding the limits of adaptations to stress. In animals, virtually all decisions taken during life are expected to have downstream consequences. To what degree rare, but energy-demanding, decisions carry over to individual performance is rarely studied in arthropods. We used spiders as a model system to test how single investments in silk use -for dispersal or predator escape -affect individual performance. Silk produced for safe lines and as threads fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For example, the altered growth and development of plants in response to wind or mechanical perturbation (thigmorphogenesis) reduces plant size and fecundity (Chehab et al, 2008; Telewski & Pruyn, 1998). Similarly, the induction of dragline spider silk production reduces spider survival and fecundity (Bonte et al., 2016). For marine bivalves, a greater cost of shell production induced by low salinity conditions can affect energetic limitation (Sanders et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the altered growth and development of plants in response to wind or mechanical perturbation (thigmorphogenesis) reduces plant size and fecundity (Chehab et al, 2008; Telewski & Pruyn, 1998). Similarly, the induction of dragline spider silk production reduces spider survival and fecundity (Bonte et al., 2016). For marine bivalves, a greater cost of shell production induced by low salinity conditions can affect energetic limitation (Sanders et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Still, even at this fine scale, immigration should differ strongly between spider groups with different behaviour. We based our high-middle-and low-mobility groups on a combination of hunting behaviour and ballooning ability, assuming that highly active hunters able to do ballooning would be most likely to perform bridging and move freely through the canopy (Asakura & Miller, 2014;Bonte et al, 2012Bonte et al, , 2016De Meester & Bonte, 2010).…”
Section: Links Between Mobility and Foraging Behaviourmentioning
confidence: 99%
“…Predator avoidance and searching for mates are probable triggering factors for short-distance dispersal events such as bridging (Aceves-Aparicio, Tapia-McClung, Macías-Ordóñez, & Rao, 2018;Bonte et al, 2009Bonte et al, , 2016 and wandering hunters are more likely to encounter predators (i.e. ants) than web builders (Gunnarsson & Wiklander, 2015;Mestre et al, 2014).…”
Section: Links Between Mobility and Foraging Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Web relocation is costly because the spider has to spend a lot of energy to build new webs after relocation (Blackledge and Wenzel 1999, Thomas et al 2003, Bonte et al 2016). For example, it has been reported that during web relocation, linyphiid spiders produce silk threads for distances of up to several hundred meters prior to ballooning (Thomas et al 2003).…”
Section: Introductionmentioning
confidence: 99%